Fear factors in cataloguing Arabic books: USM experience - Ismail, Mohd Ikhwan; Tuan Yaakub, Tuan Sira Zawana; Mohd Napiah, Mohd Kamal (2011)

(untitled)
Library as the heart of the university is developing over the years with various types of collections written and presented in many languages such as English, Malay, and Arabic. Different languages come with different letters, words, pronunciations, and characters, thus creating great challenges to the librarians. For cataloguers, determining the access point is crucial in order to ease the retrieving process. There are certain issues faced by cataloguers that should be addressed to ensure the uniformity and authoritativeness of records in cataloguing Arabic books.